Workplace Friendship and Knowledge Hiding: A Moderated Mediation Model of Psychological Safety and Task Interdependence - Shuai Wang (Forest Chemicals Review)
Previous research had focused on the influence effect of workplace friendship on knowledge sharing. However, little is known that workplace friendship might also contribute to breaking the concerns of choosing to hide and retain knowledge, leading to reducing knowledge hiding behaviours. Our purpose is to understand whether, how and when the inhibiting effect of workplace friendship on knowledge hiding is likely to unfold. Based on conservation of resources theory, we provide a moderated mediation model of psychological safety that associates workplace friendship with knowledge hiding. By analyzing the data from 455 respondents, our findings indicated that workplace friendships had a negative effect on knowledge hiding via psychological safety. We further found that the level of task interdependence moderated the indirect effect of workplace friendship on knowledge hiding via psychological safety. Overall, our research provides a theoretical and empirical foundation for future research on workplace friendship and knowledge management.